Revisiting sites of the South Pole Queen Maud Land Traverses in East Antarctica: Accumulation data from shallow firn cores - Anschütz, Helgard; Müller, Karsten; Isaksson, Elisabeth; McConnell, Joseph R.; Fischer, Helmut; Miller, Heinz; Albert, Mary; Winther, Jan-Gunnar (Journal of Geophysical Research: Atmospheres, 2009)
[1] Ground-based accumulation measurements are scarce on the high East Antarctic plateau, but highly necessary for model validation and the interpretation of satellite data for the determination of Antarctic mass balance. Here, we present accumulation results obtained from four shallow firn cores drilled in the Antarctic summer season 2007/2008. The cores were drilled along the first leg of the Norwegian-US IPY traverse through East Antarctica, visiting sites like Plateau Station and Pole of Relative Inaccessibility that have been covered by the South Pole Queen Maud Land Traverses (SPQMLT) in the 1960s. Accumulation has been determined from volcanic chronology established from the conductivity records measured by dielectric profiling (DEP). The Tambora 1815/unknown 1809 double peak is clearly visible in the conductivity data and serves as a reliable time marker. Accumulation rates averaged over the period 1815–2007 are in the range of 16 to 32 kg m−2 a−1, somewhat lower than expected from the SPQMLT data. The spatial pattern is mainly influenced by elevation and continentality. Three of the firn cores show a decrease of more than 20% in accumulation for the time period 1815–2007 in relation to accumulation rates during the period 1641–1815. The spatial representativity of the firn cores is assessed by ground-penetrating radar, showing a rather smoothly layered pattern around the drill sites. Validation of the DEP results is utilized by comparison with chemistry data, proving the validity of the DEP method for dating firn cores. The results help understanding the status of the East Antarctic ice sheet and will be important for e.g. future model-derived estimates of the mass balance of Antarctica.
Keywords: Dronning Maud Land; geofysikk; glasiologi; innlandsis; isbreer; vulkaner

Magnitude scales for very local earthquakes. Application for Deception Island Volcano (Antarctica) - Havskov, Jens; Peña, José A; Ibáñez, Jesús M; Ottemöller, Lars; Martı́nez-Arévalo, Carmen (Putting Volcano Seismology in a Physical Context. In memory of Bruno Martinelli, 2003)
Different magnitude scales are calculated for a set of volcano-tectonic earthquakes recorded in Deception Island Volcano (Antarctica). The data set includes earthquakes recorded during an intense seismic series that occurred in January–February 1999, with hypocentral distances that range between 0.5 and 15 km. This data set is enlarged to include some regional earthquakes with hypocentral distances up to 200 km. The local magnitude scale, ML, fixed at a hypocentral distance of 17 km, is used as the reference for the other magnitude scales studied in the present work. ML is determined on a standard Wood–Anderson simulated trace assuming a gain of 2080. Maximum peak-to-peak amplitudes are measured on the vertical components of a short-period sensor. The Mw scale is calculated, in the vertical component, both for P and S waves. The attenuation correction of the ground motion displacement spectra is introduced using data from coda waves studied in the area. The comparison between ML values and Mw estimations indicates severe discrepancies between both values. A magnitude–duration scale is calibrated from the comparison between coda durations of the recorded events and their assigned local magnitude scales. In order to investigate the causes of the discrepancy between the ML and Mw values we analyze two possible error sources: a wrong coda Q value, or the effects of the near-surface attenuation that initially are not taken into account in the correction of the ground displacement spectra. The analysis reveals that the main cause of this discrepancy is the effect of the near-surface attenuation. The near-surface attenuation is also the cause of the determination of an anomalous spectral decay slope, after the corner frequency, and the determination of this corner frequency value. This near-surface attenuation, represented by κ, is estimated over the data set, obtaining an average value of 0.025. With this κ value, the Mw scale is recalculated using an automatic algorithm. The new Mw values are more consistent with the ML values, obtaining a relationship of Mw=0.78ML−0.02.
Keywords: Antarktis; Deceptionøya; geologi; vulkaner

Geochronologic evidence for Early Cretaceous volcanic activity on Barton Peninsula, King George Island, Antarctica - Kim, Hyeoncheol; Ik Lee, Jong; Young Chose, Moon; Cho, Moonsup; Zheng, Xiangshen; Sang, Haiquing; Qiu, Ji (Polar Research, 2000)
Ages of six volcanic and plutonic rocks on Barton Peninsula, King George Island, were determined using 40Ar/39Ar and K-Ar isotopic systems. The 40Ar/39Ar and K-Ar ages of basaltic andesite and diorite range from 48 My to 74 My and systematically decrease toward the upper stratigraphic section. Two specimens of basaltic andesite which occur in the lowermost sequence of the peninsula, however, apparently define two distinct plateau ages of 52-53 My and 119-120 My. The latter is interpreted to represent the primary cooling age of basaltic andesite, whereas the former is interpreted as the thermally-reset age caused by the intrusion of Tertiary granitic pluton. The isochron ages calculated from the isotope correlation diagram corroborate our interpretation based on the apparent plateau ages. It is therefore likely that volcanism was active during the Early Cretaceous on Barton Peninsula. When the K-Ar ages of previous studies are taken into account with our result, the ages of basaltic andesite in the northern part of the Barton Peninsula are significantly older than those in the southern part. Across the north-west-south-east trending Barton fault bounding the two parts, there are significant differences in geochronologic and geologic aspects.
Keywords: Antarktis; geokronologi; geologi; vulkaner